From the Remainder of Adam’s Clay: Chapter Eight of Ibn al-ʿArabī’s al-Futūḥāt al-Makkiyya - Karjoo-Ravary, Ali (Journal of Sufi studies, 2021)
This article presents an introduction to and a complete English translation of the eighth chapter of Ibn al-ʿArabī’s (d. 638/1240) magnum opus al-Futūḥāt al-makkiyya. The chapter, entitled, “On the earth that was made from the remainder of Adam’s leaven clay, which is the Earth of Reality, and on some of the strange and wondrous things contained therein,” contains a description of a world wholly separate from our own. An underlying argument in this chapter is that the human intellect, constrained as it is by the categories of possibilities which pertain to our earthly configuration, is incapable of grasping the vast expanse of this “Earth of Reality.” Ibn al-ʿArabī also aims to show how many of the Qur’anic and Prophetic traditions which the intellect struggles to comprehend exist in this other world without any contradiction. In this sense, the chapter in question seeks to inculcate a sense of wonder and bewilderment in readers, reminding them that there will always be worlds, beyond our immediate sensory world, that remain to be seen and known.